Admission Dehydration Is Associated With Significantly Lower In-Hospital Mortality After Intracerebral Hemorrhage - Gao, Bin; Gu, Hongqiu; Yu, Wengui; Liu, Shimeng; Zhou, Qi; Kang, Kaijiang; Zhang, Jia; Li, Zixiao; Zhao, Xingquan; Wang, Yongjun (Frontiers in Neurology, 2021)
Background and Purpose: Our aim was to investigate the frequency of dehydration at admission and associations with in-hospital mortality in patients with intracerebral hemorrhage (ICH). Methods: Data of consecutive patients with ICH between August 2015 and July 2019 from the China Stroke Center Alliance (CSCA) registry were analyzed. The patients were stratified based on the blood urea nitrogen (BUN) to creatinine (CR) ratio (BUN/CR) on admission into dehydrated (BUN/CR ≥ 15) or non-dehydrated (BUN/CR < 15) groups. Data were analyzed with multivariate logistic regression models to investigate admission dehydration status and the risks of death at hospital. Results: A total number of 84,043 patients with ICH were included in the study. The median age of patients on admission was 63.0 years, and 37.5% of them were women. Based on the baseline BUN/CR, 59,153 (70.4%) patients were classified into dehydration group. Patients with admission dehydration (BUN/CR ≥ 15) had 13% lower risks of in-hospital mortality than those without dehydration (BUN/CR < 15, adjusted OR = 0.87, 95%CI 0.78–0.96). In patients aged <65 years, admission dehydration was associated with 19% lower risks of in-hospital mortality (adjusted OR = 0.81, 95%CI 0.70–0.94. adjusted p = 0.0049) than non-dehydrated patients. Conclusion: Admission dehydration is associated with significantly lower in-hospital mortality after ICH, in particular, in patients <65 years old.